Till [videorecording (Blu-Ray + DVD)] - Chukwu, Chinonye, 1985-; Beauchamp, Keith A.; Goldberg, Whoopi, 1955-; Reilly, Michael; Deadwyler, Danielle; Hall, Jalyn; Faison, Frankie; Carroll, Kevin (Actor); Bennett, Haley, 1988-; Lawson, Jayme, 1997-; Cole, Tosin; Thomas, Sean Patrick; et al. (Orion Releasing LLC, 2023)
Till is a profoundly emotional and cinematic film about the true story of Mamie Till Mobley's relentless pursuit of justice for her 14-year-old son, Emmett Till, who, in 1955, was lynched while visiting his cousins in Mississippi. In Mamie's poignant journey of grief turned to action, we see the universal power of a mother's ability to change the world.